Effects of a continuous remote care intervention including nutritional ketosis on kidney function and inflammation in adults with type 2 diabetes: a post-hoc latent class trajectory analysis - Athinarayanan, Shaminie J.; Roberts, Caroline G. P.; Phinney, Stephen D.; Weimbs, Thomas; Friedman, Allon N.; Volek, Jeff S. (Frontiers in Nutrition, 2025)
IntroductionDiabetic nephropathy (DN), a common complication of type 2 diabetes (T2D), is characterized by declining kidney function and an increased risk of end-stage kidney disease (ESKD). Slowing the decline in estimated glomerular filtration rate (eGFR) significantly reduces ESKD risk. While pharmacological treatments, such as SGLT2i, have demonstrated renoprotective effects, emerging evidence suggests that low-grade ketosis may mediate these benefits, and therefore be accessible through lifestyle modification.MethodsThis post-hoc analysis evaluates the impact of a very low-carbohydrate intervention including nutritional ketosis, delivered through a continuous care intervention (CCI), on eGFR slope and inflammation over two years. The analysis included 262 T2D participants in the CCI group and 87 in the usual care (UC) group. The primary aim was to assess the relationship between blood β-hydroxybutyrate (BHB) and eGFR slope. A secondary aim explored changes in inflammatory markers including high sensitivity C-reactive protein (hs-CRP) and neutrophil-lymphocyte ratio (NLR). Latent class trajectory modeling was used to categorize ketosis adherence classes in the CCI group based on longitudinal BHB levels.ResultsCCI participants experienced a significant eGFR slope increase of 0.91 mL/min/1.73m2/year, compared to a decline in UC (−0.68 mL/min/1.73m2/year). Greater mean BHB at 365 days (β = 0.1, p = 0.002) was independently associated with greater eGFR improvement that persisted after adjusting for demographics, weight change and baseline medication use. A dose–response relationship emerged between ketosis classes and eGFR improvement, particularly among participants with baseline eGFR <90 mL/min/1.73m2. Higher ketosis adherence also correlated with significant reductions in inflammatory markers, such as NLR and hsCRP, suggesting anti-inflammatory benefits.ConclusionThis analysis highlights nutritional ketosis as a potential non-pharmacological approach to improve or stabilize eGFR and reduce inflammation in T2D. Randomized controlled trials are needed to validate these findings and assess the synergistic effects of ketogenic diets combined with pharmacotherapies to optimize kidney outcomes in chronic kidney disease.